Radiolabeled nanomaterials for biomedical applications: radiopharmacy in the era of nanotechnology - Martha Sahylí Ortega Pijeira; Herlys Viltres; Jan Kozempel; Michal Sakmár; Martin Vlk; Derya İlem-Özdemir; Meliha Ekinci; Seshasai Srinivasan; Amin Reza Rajabzadeh; Eduardo Ricci-Junior; Luciana Magalhães Rebelo Alencar; Mohammed Al Qahtani; et al. (SpringerOpen, 2022)
Abstract Background Recent advances in nanotechnology have offered new hope for cancer detection, prevention, and treatment. Nanomedicine, a term for the application of nanotechnology in medical and health fields, uses nanoparticles for several applications such as imaging, diagnostic, targeted cancer therapy, drug and gene delivery, tissue engineering, and theranostics. Results Here, we overview the current state-of-the-art of radiolabeled nanoparticles for molecular imaging and radionuclide therapy. Nanostructured radiopharmaceuticals of technetium-99m, copper-64, lutetium-177, and radium-223 are discussed within the scope of this review article. Conclusion Nanoradiopharmaceuticals may lead to better development of theranostics inspired by ingenious delivery and imaging systems. Cancer nano-theranostics have the potential to lead the way to more specific and individualized cancer treatment. Graphical abstract